Cognitive and Social Effects of a Two-Week Digital Detox on Filipino Adolescents: A Quasi-Experimental Study - Lim, Sophia Gabrielle S.; Salazar, Rianna Marie C.; Tan, Hanna Lynn D.; Arcinas, Myla M. (Future Science / FSH-PH Publications, 2025)
The increasing integration of digital technologies into adolescent life has reshaped cognitive and social behavior, often leading to heightened anxiety, reduced attention spans, and excessive screen dependence. Filipino youth face unique challenges due to high digital engagement rates and cultural factors emphasizing constant connectivity. This quasi-experimental study investigated the cognitive effects of a two-week digital detox intervention among Grade 12 Senior High School students in a private university in the City of Manila. Using standardized assessments, pretest-posttest comparisons were conducted across three domains: attention, memory, and problem-solving capacity. Findings revealed statistically significant improvements in attention (t(79) = 2.03, p = 0.046, d = 0.23) and memory (t(79) = 3.16, p = 0.002, d = 0.36), though problem-solving showed no significant post-detox gains (t(79) = 1.78, p = 0.079). These results suggest that brief digital detox periods enhance self-regulatory processes such as focus and cognitive planning, particularly in high-usage individuals. Pearson correlation indicated a moderate positive association between pre-detox digital use intensity and post-intervention attentional improvements (r = 0.32, p = 0.004), indicating increased intervention responsiveness among digital-heavy users. However, the lack of significant correlations in memory and problem-solving domains suggests a need for longer, more structured interventions to yield measurable improvements in executive functioning. The study demonstrates the potential of structured digital detox routines as a viable cognitive wellness tool in high school settings. Future research should explore extended program durations and integrate psychosocial supports to maximize benefits and ensure sustained academic and social functioning improvements.